MALDI-TOF MS Pretreatment for Gram-Positive Bacteria in Routine Clinical Laboratories: Does Formic Acid Really Improve Identification? - Abdurrahman Gülmez; Ayşe Nur Ceylan; Selda Kömeç; Beyza Öncel; Kamuran Şanlı (OSMANGAZİ JOURNAL OF MEDICINE, 2026)
Accurate identification of Gram-positive bacteria by matrix-assisted laser desorption ionization–time of flight mass spectrometry (MALDI-TOF MS) may be limited by the complex structure of their cell walls. This study evaluated the impact of on-plate formic acid (FA) pretreatment on MALDI-TOF MS identification performance in a routine clinical microbiology laboratory. A total of 148 non-repetitive Gram-positive clinical isolates were analyzed using two preparation methods: direct transfer (DT) and on-plate FA pretreatment. Identification scores were compared with an emphasis on high-confidence species-level identification (log score ≥ 2.0). Statistical analyses were performed using the Wilcoxon signed-rank and McNemar tests. Overall identification rates were significantly higher with FA pretreatment than with DT (99.3% vs. 79.7%). The proportion of isolates achieving species-level identification increased from 27.1% with DT to 76.2% with FA pretreatment. Mean MALDI-TOF MS log scores for all isolates were significantly higher with FA (2.104 ± 0.186) than with DT (1.861 ± 0.265; p < 0.001). Notably, FA pretreatment also resulted in a significant increase in mean log scores among isolates that had already achieved species-level identification using DT (p = 0.001). The most pronounced improvement was observed among Staphylococcus spp., particularly coagulase-negative staphylococci, with complete concordance between DT and FA-assisted species-level identifications. In conclusion, on-plate FA pretreatment significantly enhances identification accuracy and diagnostic confidence for Gram-positive bacteria in routine MALDI-TOF MS workflows. Building on these findings, we propose a pragmatic, score-based, and species-aware diagnostic algorithm in which FA pretreatment is reflexively applied to Gram-positive isolates, yielding a DT log score < 2.0, with primary FA application recommended for staphylococci (particularly coagulase-negative species) and for less commonly encountered Gram-positive organisms.